Estudo da desidratação osmótica da cenoura (Daucus carota) em fatias - Araújo, Paulyanna Medeiros de (2010)
In the area of food dehydration, drying of vegetables has a very representative position, it has the objective to preserve the surplus of crops and began with sun drying. Among the vegetable is the carrot, which had its origin in Southeast Asia and in Brazil is a vegetable cultivated enough. The principal objective of this works is to find alternative ways for the conservation of carrot slices by osmotic dehydration with additional drying in heart. Were initially defined the best conditions of pre-osmotic dehydration (temperature, immersion time, type of osmotic solution) based on the results of humidity loss, solid gain, weight reduction and efficiency ratio of predehydrated carrots slices. The osmotic solutions used were composed by NaCl (10%) and sucrose (50 ° Brix) named DO1 and sucrose (50 ° Brix) called DO2. Was made experiment of pre-osmotic dehydration of carrot slices in two temperature levels, with complementary drying in heart with air circulation at 70 º C. Sensory analysis was performed and the study of slices dehydration osmotically and the slices without osmotic treatment. The best results were obtained with the solution DO1 60°C with immersion time of 60 min. The drying of carrot slices presented period of constant rate and decreasing rate. The osmotic pre-treatment reduced the initial humidity of carrot slices, reducing the time to the product to reach the same humidity content. Fick's model, considering the shrinkage, and the Page s model, adapt satisfactorily to experimental datas, allowing the determination of effective diffusion coefficients, consistent with the references. The results of sensory analysis of dry product, showed greater acceptance of sliced carrots with osmotic treatment